2023
DOI: 10.3390/metabo13040554
|View full text |Cite
|
Sign up to set email alerts
|

Different Diet Energy Levels Alter Body Condition, Glucolipid Metabolism, Fecal Microbiota and Metabolites in Adult Beagle Dogs

Abstract: Diet energy is a key component of pet food, but it is usually ignored during pet food development and pet owners also have limited knowledge of its importance. This study aimed to explore the effect of diet energy on the body condition, glucolipid metabolism, fecal microbiota and metabolites of adult beagles and analyze the relation between diet and host and gut microbiota. Eighteen healthy adult neutered male beagles were selected and randomly divided into three groups. Diets were formulated with three metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Finally, feces BA do not primarily reflect the physiological BA pool but are more dependent on the metabolic activity of the microbiota, which typically exhibits large interindividual variability (10,(49)(50)(51). Of note, as many secondary BAs that result from the microbial degradation of primary BAs are reabsorbed and thus also appear in the blood, the blood compartment reflects the hepatic capacity of BA synthesis, conjugation, and transport, and in addition the metabolic activity of the microbiome (9, 36,52). In this context, the determination of DCA and its taurine-conjugated form (T-DCA), both of which could be robustly detected in all dogs in blood and feces, are interesting candidates for diagnostic BA measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, feces BA do not primarily reflect the physiological BA pool but are more dependent on the metabolic activity of the microbiota, which typically exhibits large interindividual variability (10,(49)(50)(51). Of note, as many secondary BAs that result from the microbial degradation of primary BAs are reabsorbed and thus also appear in the blood, the blood compartment reflects the hepatic capacity of BA synthesis, conjugation, and transport, and in addition the metabolic activity of the microbiome (9, 36,52). In this context, the determination of DCA and its taurine-conjugated form (T-DCA), both of which could be robustly detected in all dogs in blood and feces, are interesting candidates for diagnostic BA measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Thakare et al (30) expanded the cross-species BA analysis up to eleven different species, also including beagle dogs. In most of these studies involving dogs, BA analysis was either presented individually across various matrices or as collective report combining several matrices, and most of these studies were performed only in mixed breeds or beagle dogs (17,(31)(32)(33)(34)(35)(36). However, the lack of BA profiling studies in different age groups, the low number of studies for healthy clinical patient collectives of very different dog breeds, and the poorly characterized dietary effects on the BA profile still limit our understanding of the physiological range in BA concentrations and abnormal values in disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that consistent overfeeding of dogs with a high-calorie Western diet (WD) can lead to MetS, regardless of the diet's composition (Moinard et al, 2020;Xue et al, 2022). However, these investigations in dogs have primarily focused on the metabolic issues associated with obesity (Tvarijonaviciute et al, 2012b;Peña et al, 2014;Moinard et al, 2020;Sun et al, 2023;Vecchiato et al, 2023). In both dogs and humans, obesity triggers an adipose tissue redistribution that results in an increase in visceral (vs. subcutaneous) fat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that consistently overfeeding dogs with high-calorie Western diets (WDs) leads to obesity and MetS, regardless of the diet composition (Moinard et al, 2020;Xue et al, 2022). Indeed, prior studies investigating the effects of WDs in dogs have primarily focused on metabolic dysfunction related to obesity (Tvarijonaviciute et al, 2012b;Peña et al, 2014;Moinard et al, 2020;Sun et al, 2023;Vecchiato et al, 2023). Within the context of obesity, both dogs and humans exhibit a redistribution of adipose tissue characterized by an increase in visceral fat, as opposed to subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%